Hybrid Systems: Computation and Control
DOI: 10.1007/978-3-540-71493-4_46
|View full text |Cite
|
Sign up to set email alerts
|

Automata Based Interfaces for Control and Scheduling

Abstract: We propose the use of formal languages of infinite words over the alphabet of task identifiers as an interface between control designs and software implementations. We argue that this approach is more flexible than the classical real-time scheduling framework based on periodic tasks, and allows composition of interfaces by language-theoretic operations. We show that finite automata over infinite words offer analyzable representation and can capture many interesting interface specifications such as exponential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 18 publications
0
70
0
Order By: Relevance
“…Weiss and Alur [WA07] consider automata theory to find the language that does not violate the performance requirements of a system. Then, a non-empty intersection of the scheduling automaton and performance requirements automata indicates the schedulability of the system.…”
Section: State Of the Artmentioning
confidence: 99%
“…Weiss and Alur [WA07] consider automata theory to find the language that does not violate the performance requirements of a system. Then, a non-empty intersection of the scheduling automaton and performance requirements automata indicates the schedulability of the system.…”
Section: State Of the Artmentioning
confidence: 99%
“…On the timing analysis/verification side, [5] and [6] first showed that certain control performance requirements induce scheduling specifications that are ω-regular languages. They then describe the construction of a scheduling automaton where every path leads to a schedule for a single ECU that guarantees all the individual performance requirements.…”
Section: A Related Workmentioning
confidence: 99%
“…For example, in Section IV we show how the methods presented in [17], [18], [33] are applied in the context of multi-hop control networks. Specifically, the theory of formal languages is applied for answering competing resource requirements of the loops to achieve stability of the whole system.…”
Section: J Multi-hop Control Network As Switched Systemsmentioning
confidence: 99%
“…It is also easy to verify that the probability of stability is higher than the probability of exponential stability for any parameters and . A system might be stable but converge to equilibrium slowly, while exponential stability bounds the rate of convergence from above and thus may prove more suitable for applications where fast convergence is required (see [17] for a similar discussion).…”
Section: A Permanent Failuresmentioning
confidence: 99%
See 1 more Smart Citation